Materialism and empirio-criticism. Critical comments on a reactionary philosophy. [Transl. by A. Fineberg. Checked and corrected in accordance with the Russian edition of 1945 of the Marx-Engels-Lenin In-t] (Foreign Languages Publishing House, 1947)
With bibliogr. and index.